The Importance of Socioeconomic Status as a Modulator of the Bilingual Advantage in Cognitive Ability - Naeem, Kamila; Filippi, Roberto; Periche-Tomas, Eva; Papageorgiou, Andriani; Bright, Peter (Frontiers in Psychology, 2018)
Between-group variability in socioeconomic status (SES) has been identified as a potentially important contributory factor in studies reporting cognitive advantages in bilinguals over monolinguals (the so called ‘bilingual advantage’). The present study addresses the potential importance of this alternative explanatory variable in a study of low and high SES bilingual and monolingual performance on the Simon task and the Tower of London task. Results indicated an overall bilingual response time advantage on the Simon task, despite equivalent error rates. Socio-economic status was an important modulator in this effect, with evidence that bilingualism may be particularly important in promoting speed of processing advantages in low status individuals but have little impact in high status individuals. However, there was a monolingual advantage on the Tower of London test of executive planning ability. Together, our findings run counter to the central assertion of the bilingual advantage account, that the process of multi-language acquisition confers a broad cognitive advantage in executive function. We discuss these findings in the context of socio-economic status as an important modulator in published studies advocating a bilingual cognitive advantage.